Comsol Multiphysics based calculation of contact pressure in mechanical systems - E.I. Baida (National Technical University "Kharkiv Polytechnic Institute", 2013)
In the article, a calculation technique for contact pressure in the axes of mechanical systems based on Comsol Multiphysics package is considered.